Blokchain dan AI Technology : Pembawa Perubahan Baru dalam Perspektif Akuntansi - Ela Juliyani; Hanum Nur Rahmadani; Wanda Berliandes; Zul Azmi (Akuntansi, 2024)
This paper aims to analyze blockchain and artificial intelligence technology used in accounting. This research also discusses the benefits and challenges in AI and blockchain technology. Qualitative descriptive methods were used to analyze books and journals related to blockchain and artificial intelligence in the field of accounting published between 2018-2023. The main goal is to obtain data that is relevant to the current issue. The results show that Blockchain and AI technology have new potential from an accounting perspective that includes several aspects. Data transparency and accuracy, real-time tracking, operational efficiency, predictive analysis with AI, and business model changes.